Antarctic psychological health as a space analogue - Kimberley Norris (2017)
Antarctica is one of the most extreme environments on Earth. The physical, psychological, social and technological parameters associated with this environment parallel those found in space. For this reason, Antarctica is well-recognised as a space analogue. By extension, research investigating psychological health in Antarctica has applications for supporting human wellbeing during both short and long-duration manned space missions. However, to date such research has largely overlooked the impacts on relationship dynamics with those left behind, including the family unit. Consideration of these issues is vital, as it can influence astronaut health, wellbeing and performance far beyond the confines of the family unit into the spaceflight experience itself.